Representasi Budaya Lokal dalam Konten Instagram @pariwisata_bondowoso - Rusli Akhmad Junaedi; Rahmat Firdaus Syarif; Renzi Prihantari; Divanti Medika Putri (Jurnal Inovasi Komunikasi, 2025)
Abstract. This study aims to analyze how the local culture of Bondowoso Regency is represented in the Instagram content of the @tourism_bondowoso account and to evaluate its impact on public understanding and engagement with the culture. This research focuses on the significance of social media, particularly Instagram, as a vital platform for promoting and representing local culture in Bondowoso Regency, encompassing elements such as art, cuisine, and customs, while also addressing the challenges of maintaining cultural authenticity amid globalization. This study uses a qualitative content analysis method to evaluate in depth how the local culture of Bondowoso Regency is represented in the Instagram content of @tourism_bondowoso. The results of this study show that @tourism_bondowoso's Instagram content effectively promotes and preserves local culture through attractive visual representations, but also faces challenges in maintaining cultural authenticity amid the influence of globalization. The recommendation for further research is to conduct a more in-depth study on the long-term impact of cultural representations on social media on local cultural identity and how communities manage the interaction between traditional cultural practices and emerging global trends.